Historians and the Decline - Slačálek, Ondřej (Dějiny – teorie – kritika, 2023)
The article analyses the discourse of Czech historians and authors publicly recognized as historians (historians Martin Kovář, Ivan Šedivý, and Marie Koldinská, egyptologist Miroslav Bárta, anthropologist Ivo Budil, and fiction writer Vlastimil Vondruška) who have consistently promoted ideas of the decline of the Western civilisation in the media and in their texts during the past decade. After presenting the context of conservative declinism in the West and in the Czech Republic, the article presents the most important topics in the discourse of the Czech declinist historians and authors: democracy, the welfare state, the EU, the army, and masculinity. The article goes on to analyse declinist historians´ critical views of scholarship and especially of new trends in historiography; according to Ivan Šedivý, “concepts like gender… minorities and marginal groups, post colonialism and environmentalism are the Molotov cocktails of the 21st century”. In their opinion, historiography allegedly lost its capacity to deliver an integrative narrative to society. Following this, the article analyses the epistemological assumptions of declinist historians: the idea of eternal human nature or “laws of development” of civilisations. In conclusion, the article argues that these assumptions are contradictory in terms of history as the analysis of the past in its specificity and difference (and towards conservative values of respect to this specificity), and that we can identify analogical contradiction in future-oriented focus of declinist historians as well.